Effects of the intention to hit a disguised backhand drop shot on skilled tennis performance - Iwatsuki, T.; Takahashi, M.; Van Raalte, J. L.; Mann, D. (International Journal of Sports Science & Coaching, 2016)
The purpose of this study was to examine the effect of the intention to hit a disguised backhand drop shot on tennis performance. Skilled tennis players (n = 10) were videotaped while hitting drop shots with and without instruction to disguise the shot. Results calculated via three-dimensional motion analysis indicated that disguised drop shots involved more shoulder rotation and greater transition movement forward than control condition drop shots. To disguise drop shots, tennis players used exaggerated shoulder rotation movement and moved their bodies forward. The results of this research highlight the effects on performance of skilled athletes' intention to deliver an unanticipatable drop shot. ABSTRACT FROM AUTHOR